Actuarial model and its application for implicit pension debt in China. (August 2016) - Wang, Lijian
Abstract: Whether the pension system transition is successful is closely related to the accurately accounted IPD amount and rationally solved scheme. China faces the problem of IPD with no exception. This paper uses individual cost method theory, combining Chinese pension system and its operation, builds up the implicit pension debt calculation model, then it measures the Chinese IPD quantity by statistical data. The paper finds out that the average IPD per-year is 39.404 billion Yuan in 2013–2050, the maximum is 185.053 in 2022, the minimum is 0.150 in 2050, and the accumulative IPD will sustain growth with annual growth rate of 7.06% in 2013–2050, from 119.787 billion Yuan to 1497.337 billion Yuan. Finally, this paper proposes the government to raise the legal retirement age, reduce the pension substitution rate, expand the coverage of endowment insurance, improve the investment yield of the pension fund, and so on, to compensate the IPD in China.